Respostas
respondido por:
1
Explicação passo-a-passo:
A = 36x²y¹ + 12x¹y¹
B = 3x¹y¹
[ 36x²y¹ +12x¹y¹ ]: [ 3x¹y¹]
Primeiro termo
36x²y¹ : 3x¹y¹ = + 12 x¹ ( primeira resposta)
36 : 3 = + 12
x² : x¹ = x¹ ( conserva a base e diminui expoente)
y¹ : y¹ = y^0 elimina y
Segundo termo
12x¹y¹ : 3x¹y¹ = + 4 resposta segundo termo
12 : 3 = + 4 >>>
x¹ : x¹ =conserva a base e diminui expoente > x^0 elimina x
y¹ : y¹ = idem idem >>>y^0 elimina y>>>
RESPOSTA >> 12X¹ + 4
Perguntas similares
4 anos atrás
4 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás